Overview on forest research in Africa - Sayer, Jeffrey A.; Palmer, J.R. (1995)
Long and consultative planning processes have been undertaken to develop priorities for strategic forestry research in Africa. The results have contributed to the development of CIFOR's medium-term plan, so that there seems to be a good match between Africa's needs and CIFOR's intentions. The political divisions of Africa make it difficult to achieve critical mass in public sector institutions. There should be renewed attempts to establish group-country research so as to maximize the effectiveness of the small pool of trained research staff. Institutional strengthening and human resource development needs more attention nationally and from donor agencies. Forestry research institutions should recruit staff from a wider range of disciplines or should develop partnerships with a wider range of organizations. A much greater effort in economics and social science research is required to compensate for the frequent policy failures. CIFOR seeks active collaboration with appropriate organizations in Africa.